2019
DOI: 10.1088/1742-6596/1224/1/012018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of PM emissions from wood pellet stoves with an innovative burning pot

Abstract: In this study, results of an extensive set of experiments on a wood pellet stove model equipped with innovative burning pots are presented. Tests have been performed to investigate the relations between design data and operation parameters of the stove and its emissions. In particular, carbon monoxide (CO) and particulate matter (PM) emissions are correlated to the burning-pot depth. The burning pot A, adopted by AICO S.p.A, allows to obtain near-to-zero CO emissions and low PM emissions: howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The flow rate of combustion air was adjusted by the speed of the flue gas extraction fan at the outlet of the stove. In its standard configuration, the stove was equipped with the "type A" burner pot described by Polonini et al [9] and patented by AICO S.p.A. [37]. In the tests carried out for the present study, the stove has been equipped with a deeper burner pot, identified as "type B" [9] and illustrated in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The flow rate of combustion air was adjusted by the speed of the flue gas extraction fan at the outlet of the stove. In its standard configuration, the stove was equipped with the "type A" burner pot described by Polonini et al [9] and patented by AICO S.p.A. [37]. In the tests carried out for the present study, the stove has been equipped with a deeper burner pot, identified as "type B" [9] and illustrated in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…In its standard configuration, the stove was equipped with the "type A" burner pot described by Polonini et al [9] and patented by AICO S.p.A. [37]. In the tests carried out for the present study, the stove has been equipped with a deeper burner pot, identified as "type B" [9] and illustrated in Figure 1. The use of this model of burner pot was previously found to be associated with lower CO and PM emissions if compared with traditional, less deep components [9].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations